External surfactant-free waterborne polyurethane grafted fluorine-containing acrylic copolymer with high hardness and low water absorption using chlorinated soybean oil-based urethane acrylate as polyol. Issue 17 (2nd September 2021) - Li, Xiaowei; Zhao, Ting; Wang, Huimin; Chu, Xiaomeng; Xing, Xuteng; Liu, Shaojie; Tang, Erjun; Xu, Xiaodong
Abstract: In this work, a novel soybean oil-based urethane acrylate polyol called ADSO was synthesized by the condensation reaction of hydroxyethyl acrylate modified isophorone diisocyanate with chlorinated soybean oil (SOL). The soybean oil-based waterborne polyurethane called ADSO-WPU was prepared with SOL and ADSO as polyols. Using the carbon-carbon double bonds of ADSO-WPU as reaction sites, methyl methacrylate (MMA), butyl methacrylate (BA) and 2-(perfluorohexyl)ethyl methacrylate (PFOMA) were grafting copolymerized to obtain the soybean oil-based waterborne polyurethane grafted fluorine-containing acrylate (ADSO-PUA). The results of Fourier transform infrared spectrometer, dynamic light scattering analyzer and transmission electron microscopy showed that the grafted copolymer latex was successfully prepared with particle size of about 100–300 nm. Furthermore, effects of the ratio of PFOMA, MMA and BA on properties of grafted copolymer films were studied. Compared with ADSO-WPU film, ADSO-PUA film had significantly lower water absorption, higher hardness, better mechanical properties and higher thermal stability. With the increase of PFOMA content, the water absorption rate decreased from 108% to about 10%, the hardness increased from 4H to 6H, and the tensile strength increased from 3.05 MPa to 9.79 MPa.